Laparoendoscopic single-site versus conventional transperitoneal laparoscopic pyeloplasty: A prospective randomized study - İLBEY, YUSUF ÖZLEM; Tugcu, Volkan; Ilbey, YUSUF ÖZLEM; Sonmezay, Erkan; ARAS, BEKİR; Tasci, Ali Ihsan (My University, 2013)
ObjectivesTo evaluate the potential benefits of laparoendoscopic single-site pyeloplasty over conventional laparoscopic pyeloplasty.